Análise de problemas da elasticidade tridimensional pelo método dos elementos de contorno com a utilização da solução fundamental de Mindlin - Hijjar, Jorge Roberto Abrahão (1987)
This work deals with the analysis of threedimensional elasticity problems with the boundary element method using Mindlin's fundamental solution. Hence, a theoretical formulation and a computer program based on it were developed. Since Mindlin's fundamental solution is for a half-space, a good efficiency in the solution of that kind of problems is obtained. The final results of the analysis are displacements and tractions on the boundary of the body and displacements and stresses at internal points. Finally, some test cases are analysed and conclusions are presented.